Regularity properties and integral inequalities related to (k; h1; h2)-convexity of functions - Cristescu Gabriela; Găianu Mihail; Muhammad Uzair Awan (Annals of the West University of Timisoara: Mathematics and Computer Science, 2015)
The class of (k; h1; h2)-convex functions is introduced, together with some particular classes of corresponding generalized convex dominated functions. Few regularity properties of (k; h1; h2)-convex functions are proved by means of Bernstein-Doetsch type results. Also we find conditions in which every local minimizer of a (k; h1; h2)-convex function is global. Classes of (k; h1; h2)-convex functions, which allow integral upper bounds of Hermite-Hadamard type, are identified. Hermite-Hadamard type inequalities are also obtained in a particular class of the (k; h1; h2)- convex dominated functions.